A Study of the Relations between Lithuania and Russia, or why “Normal” Relations are not yet to Come - Jakniūnaitė, Dovilė (Sociologija. Mintis ir veiksmas, 2008)
Review: Vitkus, Gediminas. 2006. Diplomatinė aporija: tarptautinė Lietuvos ir Rusijos santykių normalizacijos perspektyva. Vilnius: Vilniaus universiteto leidykla.